2022
DOI: 10.1186/s12860-022-00452-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of the TGF-β/LIF signaling pathway mediated by SMADs during the cyst formation of Echinococcus in young children

Abstract: Objective The present study aims to explore the correlation of the transforming growth factor β (TGF-β), drosophila mothers against decapentaplegic protein gene (SMAD) 2/3/4, and leukemia inhibitory factors (LIF) with the cyst formation of hepatic Echinococcus granulosus in young children. Methods A total of 40 patients who met the diagnostic criteria for children's hydatid disease in people's Hospital of Xinjiang Uygur Autonomous Region between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…TGF-beta superfamily ligands play an important role in the development and physiology of different animal species, among which TGF-beta signaling may be closely related to tumor progression (Gigante et al, 2012;Larson et al, 2020). TGF-beta signaling plays an important role in early embryonic development as well as in tissue and organ formation, immune surveillance, and the balance between tissue repair and homeostasis in the adult body (Heldin et al, 1997;Feng and Derynck, 2005;Qin et al, 2022;Li et al, 2023). The results of this study showed that in G vs LG, Myc protein genes were up-regulated in the "TGF-beta signaling" and "Wnt signaling" pathways.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-beta superfamily ligands play an important role in the development and physiology of different animal species, among which TGF-beta signaling may be closely related to tumor progression (Gigante et al, 2012;Larson et al, 2020). TGF-beta signaling plays an important role in early embryonic development as well as in tissue and organ formation, immune surveillance, and the balance between tissue repair and homeostasis in the adult body (Heldin et al, 1997;Feng and Derynck, 2005;Qin et al, 2022;Li et al, 2023). The results of this study showed that in G vs LG, Myc protein genes were up-regulated in the "TGF-beta signaling" and "Wnt signaling" pathways.…”
Section: Discussionmentioning
confidence: 99%